Impact of deltamethrin on the endophytic fungal community of a Chinese cabbage, Brassica chinensis. Issue 3 (15th March 2016) - Zhou, Shengliang; Qiu, Hui; Feng, Chengcheng; Guo, Yanhua; Wang, Xiaoning; Chen, Caifa
ABSTRACT: Endophytic fungi, being closely associated with their host plants, are an important part of the ecosystem and food web. In modern agriculture, pesticides are widely used. The impact of pesticides on the endophytic fungal community of crops remains poorly understood. In this paper, Chinese cabbage Brassica chinensis, a popular leafy vegetable consumed worldwide, was selected for evaluating the potential effects of a pesticide, deltamethrin, on the endophytic fungal community. By culture method, 195 endophytic fungal strains classified into 39 taxa and 186 strains classified into 30 taxa, respectively, were isolated from the pesticide-treated and untreated B. chinensis samples. Sirodesmium spp. were the predominant endophytic fungi from both samples. The colonisation rates of endophytic fungi of the treated and the untreated samples were not significantly different, as determined by one-way analysis of variance ( p > .05). The Shannon diversity indexes ( H′ ) were close, being 2.216 and 2.152, respectively. However, the endophyte compositions of the treated and the untreated samples were significantly different ( p < .01) by the canonical correspondence analysis. The similarity coefficient of the endophyte assembles was only 29.0%. Our results indicate that the application of deltamethrin lead to the change of the endophytic fungal assemble in B. chinensis .